Concise enantioselective synthesis of (+)-FR66070 and (+)-FR900482 and the synthesis and biochemical studies of a photo-triggered FR900482 mitosene progenitor - Judd, Ted Charles, author; Williams, Robert M., advisor (Colorado State University. Libraries, 2003)
The total synthesis of the natural products (+)-FR66979 and (+)-FR900482 is presented. The synthesis features a novel dimethyldioxirane-mediated reaction for construction of the hydroxylamine hemiketal functionality and represents the shortest total synthesis reported to date. The synthesis of a photo-triggered mitosene progenitor based on the natural products (+)-FR66979 and (+)-FR900482 has also been described. Biochemical studies demonstrate the capacity of the mitosene progenitor to form DNA interstrand cross-links upon photo-activation. Furthermore, the cross-links have been shown to share the identical sequence specificity as the natural products.
Keywords: Enantioselective catalysis; Antineoplastic agents; Organic compounds -- Synthesis